Impacto de las redes sociales en la construcción de la identidad social en un adolescente de 16 años (2023)
In the current digital age, social media has become an integral part of adolescents' lives, playing a significant role in the formation of their social identity. This research focuses on analyzing the impact of social media on the social identity construction processes of a 16-year-old adolescent from Tuluán. To this end, a systematic review of the existing literature was conducted, with an emphasis on relevant empirical and theoretical studies.